2013
DOI: 10.3233/ch-131688
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and metabolic determinants of blood rheology differ between trained and sedentary individuals

Abstract: Body composition and nutrition have been reported to be correlated with blood rheology. However, in sedentary and in physically active individuals these relationships seem to be not exactly similar. This study investigated whether exercise training status influences these relationships. 32 athletes (ATH) (age: 25 ± 0.7 yr; body mass index (BMI): 23.75 ± 0.23 kg/m²) were compared to 21 sedentary subjects (SED) (age: 45.19 ± 2.90; BMI = 33.41 ± 1.33) with nutritional assessment (autoquestionnaire), bioelectrical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
0
6
0
1
Order By: Relevance
“…In our study, although the sample was sedentary at the beginning of the intervention (<30 min physical activity/day), subjects who started the program with more daily steps presented an increase in protein intake, although diet recommendations were equal for all the participants. Other studies have shown that active individuals consumed more protein than inactive counterparts [10,29]. This fact could be related to the belief that active individuals need to consume more proteins than sedentary individuals [10].…”
Section: Discussionmentioning
confidence: 97%
“…In our study, although the sample was sedentary at the beginning of the intervention (<30 min physical activity/day), subjects who started the program with more daily steps presented an increase in protein intake, although diet recommendations were equal for all the participants. Other studies have shown that active individuals consumed more protein than inactive counterparts [10,29]. This fact could be related to the belief that active individuals need to consume more proteins than sedentary individuals [10].…”
Section: Discussionmentioning
confidence: 97%
“…ingly, in physiological conditions, RBC rigidity is positively correlated with carbohydrate intake in trained athletes [117]. Presumably, this physiological effect does not have the same significance as the red cell stiffening induced by chronic hyperglycemia.…”
Section: Rbcs and Their Energy Needsmentioning
confidence: 97%
“…In fact, in normal red cells, glucose deprivation (energy crisis) [20,24], rather than hyperglycemia, induces irreversible red cell damage and eryptosis [115,116]. Interestingly, in physiological conditions, RBC rigidity is positively correlated with carbohydrate intake in trained athletes [117]. Presumably, this physiological effect does not have the same significance as the red cell stiffening induced by chronic hyperglycemia.…”
Section: Rbcs and Their Energy Needsmentioning
confidence: 99%
“…RBC rigidity is also positively correlated with carbohydrate intake in trained athletes, in whom positive correlations are evidenced between caloric (and CHO) intake and both RBC rigidity and aggregability [37].…”
Section: Carbohydrate Metabolismmentioning
confidence: 89%